Prospects for a Common Morality. - Outka, Gene (Princeton University Press, 2001)
This volume centers on debates about how far moral judgments bind across traditions and epochs. Nowadays such debates appear especially volatile, both in popular culture and intellectual discourse: although there is increasing agreement that the moral and political criteria invoked in human rights documents possess cross-cultural force, many modern and postmodern developments erode confidence in moral appeals that go beyond a local consensus or apply outside a particular community. Often the point of departure for discussion is the Enlightenment paradigm of a common morality, in which it is as.